2012
DOI: 10.1007/s00246-012-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Left Atrial Isomerism at a Single Institution

Abstract: Left atrial isomerism includes a complex spectrum of cardiac and extracardiac anomalies. The records of all patients with left isomerism born during the period of 1973-2010 and treated at the Children's Hospital, Helsinki were reviewed. The short- and long-term outcomes were studied. The review included 38 patients (50% females). The overall survival with left atrial isomerism was 63% during a median follow-up time of 16 years (range, 4-30 years). Extracardiac anomalies were noted in 14 (37%) of 38 cases. Card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
1
19
1
Order By: Relevance
“…In the PSP group, the survival with a biventricular circulation was significantly higher than previously reported. 3,10 Although the survival for both ASP and PSP of continued pregnancies in our study was slightly better than previously reported (44% vs 12% to 21% for ASP 12,15 and 79% vs 39% to 61% in PSP 1,12,13,15 ), the prognosis for patients with HS is still dismal, especially for those with ASP. The improvement in our survival rate can be explained by a most recent era analyzed and in the case of PSP by the inclusion of a high proportion of normal hearts.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In the PSP group, the survival with a biventricular circulation was significantly higher than previously reported. 3,10 Although the survival for both ASP and PSP of continued pregnancies in our study was slightly better than previously reported (44% vs 12% to 21% for ASP 12,15 and 79% vs 39% to 61% in PSP 1,12,13,15 ), the prognosis for patients with HS is still dismal, especially for those with ASP. The improvement in our survival rate can be explained by a most recent era analyzed and in the case of PSP by the inclusion of a high proportion of normal hearts.…”
Section: Discussioncontrasting
confidence: 81%
“…Our results support the previously published data that pulmonary vein stenosis and noncardiac anomalies strongly affect the survival for HS patients. 3,4,8,10,12,13,28 In our cohort, only 5 patients with TAPVC are still alive, all of them <2 years. Therefore, for ASP patients with TAPVC, prenatal counseling should describe the potential for pulmonary vein stenosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Biventricular repair with a 2-patch method is usually performed for the complete type of AVSD with balanced ventricles. 79 AVSD with unbalanced ventricles is sometimes seen in patients with left isomerism, where either of the ventricles and the inflow tract is significantly hypoplastic, for instance in less than 30%. 80 In these cases, biventricular repair is not feasible.…”
Section: Left Isomerismmentioning
confidence: 99%
“…Respiratory disorders can include tracheoesphageal fistula and absence of one lung. Neurologic disorders include myelomeningocoele and en-Williams-Phillips and Hoo Sang (3,4).…”
Section: Learning Objectivesmentioning
confidence: 99%